PROGRAM PENGEMBANGAN KOMUNIKASI GURU DENGAN SISWA TUNARUNGUDI SEKOLAH INKLUSI - Siti Musayaroh, - (2018)
Masalahkomunikasi yang mengganggu aktivitas kelas cenderungtimbulketikaterdapat kehadiran siswa tunarungu di kelas inklusi karena belum adanya kesepakatan komunikasi diantara guru dan siswa tunarungu.Penelitian ini bertujuanmerumuskan program pengembangan komunikasi guru dengan siswa tunarungu di sekolah inklusi. Subjek penelitian adalah tiga guru kelas dan empat guru mata pelajaran serta enam siswatunarungu dengan hambatan pendengaran berat dan tanpa mempunyai hambatan ganda. Observasi, wawancara, dan dokumentasi digunakan untuk menggali kemampuankomunikasisiswatunarungudankondisi objektif komunikasi guru dengan siswa tunarungu di kelas inkusi.Hasil analisis data menunjukkankomunikasi antara guru dengan siswa tunarungu di sekolah inklusi cenderung dilakukan secara lisan dengan membaca ujaran dan bantuan teman sebaya. Rumusan program pengembangan komunikasiguru dengan siswa tunarunguberisi konsep ketunarunguan yang meliputi klasifikasi tunarungu dan dampaknya dalam komunikasi, penerapan prinsip-prinsip komunikasi dengan siswa tunarungu, pemilihan pendekatan komunikasi yang tepat dan pengelolaan pembelajaran yang aktif untuk semua siswa.Untuk itu, komunikasi tatap muka dan kejelasan artikulasi adalah kunci dari prinsip keterarah wajahan dan keterarah suaraan. Prinsip keperagaan dan totalitas membutuhkan persiapan khusus seperti menyiapkan media audio-visual, gambar, benda tiruan dan asli.Memberikan kesempatan siswa tunarungu mengungkapkan pendapat dan mempresentasikan hasil pekerjaan dapat mendorong terlaksananya prinsip tanggap dengan apa yang dikatakan siswa tunarungu dan dorongan imitasi. Selanjutnya, penggunaan isyarat, gerak tubuh, ekspresi, menunjuk gambar atau benda, tulisan dan berbicara lisan secaraserempak sangat membantu komunikasi guru dengan siswa tunarungu.----------------------------------------Communication problems that disrupt classroom activities tend to arise when there is a presence of deaf students in the inclusive class because there has not been a communication agreement among teachers and deaf students. This study aims to formulate a program for developing communication skills for teachers with deaf students in inclusive schools. The subjects of the study were three classroom teachers, four subject teachers and six deaf students with profound category and without multiple barriers. Observations, interviews, and documentation were used to explore the communication skills of deaf students and the objective conditions of teachers' communication with deaf students in the inclusive class. The results of data analysis showed that communication between teachers with deaf students in inclusion schools tended to be done orally by reading speech and peer assistance. The formulation of program for developing communication skills for teacher with deaf students contains concept of deafness which includes deaf classification and its impact in communication, application of communication principles with deaf students, selection of appropriate communication approach and active learning management for all students. Dealing with this, face-to-face communication and articulation clarity are considered to be the keys for the principle of facial explanation and voice activation. Furthermore, the principles of visual aid use and totality require special preparation such as preparing audio-visual media, images, artificial and authentic objects. Giving deaf students opportunities to express their opinions and presenting the result of their works can encourage the implementation of principles of responsive with what deaf students say and impulse imitations. Moreover, the use of signing, gesture, expressions, pictures or objects pointing, as well as written and spoken language simultaneously will greatly assist the communication of teachers with deaf students.